A Metáfora na construção de sentidos pela criança com perda auditiva de grau moderado - Albuquerque, Katia Maria Gomes de (2004)
This study analyses metaphor comprehension by children with moderate hearing loss, individuais who are located at an intermediate zone between listeners and more severely deaf children. They recognize themselves as speakers and Iisteners, although their oral language acquisition channel -the articulate-acoustic -has a receptive limitation. 80, there are some concerns such as: if the limitation causes lacks on the interactive changes oportunities that interfere on the metaphorical comprehension. The sample consisted of two children with moderate hearing loss, nine to twelve years-old, hearing aids users, undergoing speech therapy and attending private schools. The research procedure was the oral presentation of twelve metaphors inserted in brief stories to each of the participant, when they were questioned about the constructed meaning of the metaphor comprehension and which were the strategies used for such understanding. Metaphor analysis was based on the Conceptual Metaphor Theory by Lakoff and Johnson (1980, 2002) and it was observed if the constructions made by the children agreed with the meaning suggested by the utterance. We found out, after data analysis, that the children with moderate hearing loss, even though they are at the age that we expect them to be able to comprehend and to explain the metaphorical process of meaning construction, they had difficulty with these skills. We hope that, with this study, we can contribute to the knowledge of these individuais with hearing loss, in their interactive and linguistic particularities, as they are subjects that have been little dealt with in the literature, and that we can contribute to improving their speech therapeutic and educacional needs